2017
DOI: 10.1108/sbm-01-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

How fans are engaging with baseball teams demonstrating multiple objectives on Instagram

Abstract: Purpose Using uses and gratifications theory as a guide, the purpose of this paper is to examine how fans are engaging with Major League Baseball (MLB) teams that are utilizing Instagram postings to demonstrate sporting, business, and social objectives. Design/methodology/approach An analysis of 1,500 photos (50 from each team) was conducted. A content analysis analyzed the content of the photo, and a textual analysis was implemented to examine the use of hashtags by the teams on their Instagram photos. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
2
17
0
1
Order By: Relevance
“…Relating the relationship between type of post, it is striking that images, besides being much more abundant, are less effective than videos when it comes to generating comments and similar effective on generating likes, this could be due Instagram is still understood by athletes as a photography social media. The use of hashtags (#), mentions (@) or emoticons do not seem to have much incidence in the interaction with audiences; this result is consistent with other previous investigations such as those of Geurin-Eagleman and Burch (2016) or Kim and Hull (2017), which even detect a negative correlation between the use of hashtags and mentions with the number of likes and comments.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Relating the relationship between type of post, it is striking that images, besides being much more abundant, are less effective than videos when it comes to generating comments and similar effective on generating likes, this could be due Instagram is still understood by athletes as a photography social media. The use of hashtags (#), mentions (@) or emoticons do not seem to have much incidence in the interaction with audiences; this result is consistent with other previous investigations such as those of Geurin-Eagleman and Burch (2016) or Kim and Hull (2017), which even detect a negative correlation between the use of hashtags and mentions with the number of likes and comments.…”
Section: Discussionsupporting
confidence: 90%
“…Geurin-Eagleman and Burch (2016) show how athletes use this social network as a tool to build their personal image, finding a relation between the engagement with the variety of photos and noting that sexually suggestive posts reach a greater number of likes and comments. Likewise, Kim and Hull (2017) states that baseball team followers on Instagram engage more (with comments and likes) to posts related to sports issues than to those that have to do with social or business issues. Other recent studies focus on specific aspects such as the use of Instagram to challenge or reinforce gender stereotypes (Pegoraro et al, 2018) or strategies to attract Hispanic followers, in the case of baseball, through the use of language (Hull et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Others have investigated how sport leagues can use YouTube for agenda-setting purposes (Zimmerman, Clavio, & Lim, 2011). Recent studies have examined how Instagram can be used for engaging fans for sporting, business as well as social objectives (Kim & Hull, 2017); as a self-presentation tool by Olympic athletes specifically (Geurin- Eagleman & Burch, 2016), or by professional athletes more generally (Smith & Sanderson, 2015). More in relation to the present study, yet outside the professional teams' context, Geurin- Eagleman and Burch (2017) found that sport brands that utilise user-generated content on their Instagram accounts elicit higher engagement from followers when posts have an overt focus on the product.…”
mentioning
confidence: 99%
“…Among the online venues readily available these days, Instagram occupies a powerful position. Citing Elliott (), Kim and Hull (, p. 216) assert that ‘Instagram's per‐follower engagement rate (or total number of likes, comments, or shares on a post) is more than ten times greater than Facebook and more than 100 times greater than Twitter.’ This study will look at Instagram, which needs attention from sociolinguists considering its significant role in many online users’ daily linguistic activities. Regarding sport fan identity, most studies discuss group sports and expert or quasi‐expert discourse (see Cox, for research on sports blogging and the Detroit Red Wings hockey blog Winging it in Motown ).…”
Section: Online Fan Discoursementioning
confidence: 99%